Magnetostratigraphy and Palaeoclimatic Significance of the Late Pliocene Red Clay‐Quaternary Loess Sequence in the Lanzhou Basin, Western Chinese Loess Plateau. Issue 3 (5th February 2020) - Guo, Benhong; Peng, Tingjiang; Yu, Hao; Hui, Zhengchuang; Ma, Zhenhua; Li, Xiaomiao; Feng, Zhantao; Liu, Jia; Liu, Shanpin; Zhang, Jun; Ye, Xiyan; Song, Chunhui; et al.
Abstract: The history of red clay‐loess accumulation in the Chinese Loess Plateau (CLP) is the key to understanding the aridification history of the Asian interior and the uplift of the Tibetan Plateau. Here we present high‐resolution magnetostratigraphy and grain‐size records of a 265.7‐m‐long drill core of the red clay‐loess sequence at Gaolanshan in the Lanzhou Basin from the western CLP. Our results, combined with the loess‐paleosol stratigraphy and regional stratigraphic correlation, indicate that the most complete and continuous red clay‐loess sequence since ~3 Ma was first found in the western CLP, which is ~0.8 Myr older than the previously investigated Quaternary loess in the Lanzhou region, and the age of the oldest Lanzhou loess‐paleosol sequence is ~2.8 Ma. Consequently, the major enhancement of the aridification at 2.8 Ma in the Asian interior was primarily controlled by the uplift of the Tibetan Plateau and global cooling. Plain Language Summary: The deposition of eolian loess in the Chinese Loess Plateau provides critical information for understanding the aridification history of the Asian interior and the uplift of the Tibetan Plateau. However, eolian deposits in the Lanzhou Basin of the western Chinese Loess Plateau dated to the interval of 3.6–2.2 Ma have rarely been studied, which hinders our understanding of the process of regional aridification and the history of tectonic activity. High‐resolution magnetostratigraphy, grain‐size records, loess‐paleosol stratigraphy, and regional stratigraphic correlation suggest that the basal age of the Gaolanshan drill core is ~3 Ma, which is some 0.8 Myr older than the previously investigated Quaternary loess in the Lanzhou region. The age of the base of the typical loess‐paleosol deposits in the Lanzhou area is ~2.8 Ma. A synthesis of other eolian sections reveals that the Lanzhou loess is one of the most complete and continuous continental sedimentary archives for reconstructing climatic evolution since the Late Pliocene. Pronounced increases in grain size and sedimentation rate in loess layer L34 indicate an enhancement of aridity at 2.8 Ma in the Asian interior, and we conclude that this event was likely driven by both tectonic activity and global cooling. Key Points: The red clay‐loess sequence since ~3 Ma was first found in the Lanzhou Basin, western Chinese Loess Plateau The pronounced increase in grain‐size and sedimentation rate at 2.8 Ma supported the intensified aridification in the Asian interior This obvious aridification was primarily caused by the uplift of the Tibetan Plateau and global cooling